(x+y^2)^2-(y^2-2)(y^2+2)-2xy^2 упростите выражение и найдите его значение при х=-5

2

Ответы и объяснения

2013-05-05T23:28:22+04:00

(x+y^2)^2-(y^2-2)(y^2+2)-2xy^2=x^2+2xy^2+y^4-(y^2-2)*(y^2+2)-2xy^2=x^2+2xy^2+y^4-(y^4-4)-2xy^2=x^2+2xy^2+y^4-y^4+4-2xy^2=x^2+2xy^2+4-2xy^2=x^2+4


x^2+4=(-5)^2+4=25+4=29

2013-05-05T23:30:29+04:00

(x+y^2)^2-(y^2-2)(y^2+2)-2xy^2 = x^2+2xy^2+y^4-(y^2-2)*(y^2+2)-2xy^2 = x^2+2xy^2+y^4-(y^4-4)-2xy^2 = x^2+2xy^2+y^4-y^4+4-2xy^2=x^2+2xy^2+4-2xy^2=x^2=(-5)^2+4=25+4=29

как-то такс